Chemical modification of bamboo activated carbon surface and its adsorption property of simultaneous removal of phosphate and nitrate. (January 2022) - Shao, Yanan; Li, Jianmin; Fang, Xiuying; Yang, Zhie; Qu, Yuelin; Yang, Min; Tan, Wei; Li, Guizhen; Wang, Hongbin
Abstract: Zr/CTAB/BAC was prepared by bamboo activated carbon (BAC) functionalised by zirconia chloride octahydrate (ZrOCl2 ·8H2 O) and Cetyltrimethylammonium bromide (CTAB). The effects of temperature, time, Zr dosage and CTAB concentration on removing phosphate and nitrate (H2 PO4 − and NO3 − ) in wastewater were investigated. The structure of Zr/CTAB/BAC was characterized by SEM, BET, FTIR, XRD and TG, and the kinetics and thermodynamics of adsorption were discussed. The optimum preparation conditions were as follows: the modification temperature was 25 °C, the modification time was 4 h, the mass of the modifier Zr added was 0.40 g, and the concentration of the modifier CTAB was 0.6 mM. When the dosage of Zr/CTAB/BAC was in the range of 0.1 g–1.0 g, the removal efficiency of phosphate in simulated wastewater was between 59.32% and 99.42%, and the removal efficiency of nitrate was between 34.08% and 93.70%. Using NaOH as a regenerant, after four times adsorption and desorption experiments, the removal efficiency of phosphate and nitrate by Zr/CTAB/BAC can still reach more than 70%. The chemical adsorption was the primary cause of the adsorption, and the adsorption process was endothermic. Zr/CTAB/BAC had an obvious removal effect on phosphate and nitrate in water, which could be promoted to treat other anionic salts in sewage. Highlights: Zr/CTAB/BAC could maintain high adsorption efficiency for phosphorus and nitrogen in wastewater after four times of reuse. The mechanism of Zr/CTAB/BAC carbon material to simultaneously remove phosphate and nitrate in wastewater is discussed. A new way of bamboo (a renewable resource) application was established.